Longitudinal evaluation of azithromycin and cytokine concentrations in amniotic fluid following one‐time oral dosing in pregnancy - Rupsa C. Boelig; Edwin Lam; Ankit Rochani; Gagan Kaushal; Amanda Roman; Walter K. Kraft (Wiley, 2021)
Abstract To utilize noninvasive collection of amniotic fluid in the setting of preterm premature rupture of membranes (PPROMs) to report the time concentration profile of azithromycin in amniotic fluid over 7 days from a single dose, and evaluate the correlation between azithromycin concentration and inflammatory markers in amniotic fluid. Prospective cohort study of five pregnant patients admitted with PPROMs and treated with a single 1 g oral azithromycin dose. Amniotic fluid was collected from pads and used to quantify azithromycin concentration as well as TNFa, IL‐1a, IL‐1b, IL‐6, IL‐8, and IL‐10 concentrations. Primary outcome was time/concentration profile of azithromycin in amniotic fluid. Secondary outcome included correlation between azithromycin concentration and cytokine concentrations. Five patients were enrolled. Mean gestational age on admission with PPROM was 27.5 ± 2.3 weeks with a median latency of 7 days (interquartile range [IQR] = 4-13). A median of two samples/day (IQR = 1-3) were collected per participant. Azithromycin was quantified in duplicate; intra‐assay coefficient of variation was 17%. Azithromycin concentration was less than 60 ng/ml after day 3. Azithromycin concentration was positively correlated with IL‐8 (r = 0.38, p = 0.03), IL1a (r = 0.39, p = 0.03), and IL‐1b (r = 0.36, p = 0.04) in amniotic fluid. Azithromycin is detectable in amniotic fluid over 7 days from a single 1 g maternal dose, however, it is not sustained over the range of minimum inhibitory concentration for common genitourinary flora. Based on correlation with specific cytokines, azithromycin penetration in amniotic fluid may relate to maternal monocyte concentration in amniotic fluid in the setting of PPROM.